The Digital Technology-Based Learning Media in Indonesian Language Education at Elementary Schools: A Systematic Literature Review - Pebriana, Putri Hana; Sari, Cindy Fatika; Anggraini, Nadia Fahira; Pohan, Ratih Nurjannah; Afifah, Rifdah; Febriani, Amelia; Fitrah, Dinia Ahira; Annisa, Nur (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study was conducted to investigate the utilization of digital technology-based learning media in teaching the Indonesian language at elementary schools using the Systematic Literature Review (SLR) approach. The research methodology involves the analysis of scientific articles, both from domestic and international sources, published in the last 5–10 years and sourced from indexed databases. The review process includes the steps of identification, selection, evaluation, and analysis of articles based on predetermined criteria for inclusion and exclusion. The findings indicate that digital technology-based learning media, such as interactive multimedia, educational videos, educational apps, and online learning platforms, have a positive impact on increasing students' motivation, understanding of the material, and language skills in elementary schools. Furthermore, the use of digital media can create a more engaging, relevant, and student-centered learning experience. However, there are several challenges, including limited facilities, low digital competence among teachers, and unequal access to technology. Therefore, policy support, continuous teacher training, and adequate infrastructure provision are needed to maximize the use of digital technology-based learning media in Indonesian language education at elementary schools.